THE MEANING OF EXISTENCE AND THE MATTER OF FATE IN THE NOVEL “OF HUMAN BONDAGE” (International Conference on Education, Psychology and Humanities, 2026)
This article analyzes the artistic expression of human destiny and existential problems in the novel “Of Human Bondage” by the English writer Somerset Maugham. The work raises questions about human existence, freedom, and the meaning of life through the life quests, choices, and sufferings of the main character Philip Carey. The main concepts of existential philosophy — self-awareness, the search for meaning, loneliness, absurdity, and responsibility for choice — become central themes in the poetics of the novel. The article sheds light on the place of Maugham’s work in the existential context and the writer’s concept of destiny from an artistic and philosophical perspective.
Keywords: existentialism, destiny, choice, freedom, responsibility, meaning of life, Somerset Maugham, Philip Carey, absurd.